Reconstruction of Traffic Norms Regarding the Presence of Vehicles with Auto Driving Technology - Ryan Adhi Pradana; Muchlas Rowi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of autonomous vehicle technology has significantly disrupted conventional traffic systems, which have traditionally treated humans as the primary controllers and legal subjects. This study analyzes gaps in national traffic regulations concerning autonomous vehicles, examines the legal implications of the technology, and proposes regulatory updates to better address ongoing technological developments. The research method employs a qualitative approach with a normative and conceptual approach. The normative approach is carried out by reviewing Law Number 22 of 2009 on Road Traffic and Transportation. This conceptual approach compares classical legal liability theories with the frameworks of risk-based liability and product liability in the context of autonomous vehicles. This study also examines regulatory models in the United States, Germany, and Japan to gain an international perspective on the division of responsibility, safety standards, and technology oversight. The research findings indicate that conventional traffic norms have significant limitations in determining driver status, proving violations, and the responsibility of technology manufacturers. This normative vacuum creates legal uncertainty and safety risks for road users. The research emphasizes the urgency of reconstructing traffic norms, including redefining the concept of driver, regulating technological risk-based liability, and strengthening the precautionary principle and legal accountability. The results of this study are expected to serve as a basis for policymakers and law enforcement officials in developing regulations that adapt to autonomous vehicles and ensure legal certainty and public safety.